2014
DOI: 10.5114/wiitm.2014.47642
|View full text |Cite
|
Sign up to set email alerts
|

A risk score to predict the difficulty of elective laparoscopic cholecystectomy.

Abstract: IntroductionSeveral preoperative scoring systems have been proposed to predict the difficulty of laparoscopic cholecystectomy in order to optimize the results of surgical treatment by either selection of patients for the procedure or providing an adequately experienced surgical team for a given patient. Nevertheless, none of them has achieved significant penetration into everyday practice.AimTo propose and validate a novel risk score based on the patient's history, physical examination and abdominal ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 12 publications
0
32
0
3
Order By: Relevance
“…[9,10] Pre-operative prediction becomes more important so that surgeons can be requested to be present during surgery and to avoid unnecessarily prolonging the surgery and to prevent complications. [11] In the present study, difficult LC was significantly more in patients with a history of previous abdominal surgery, tenderness in right hypochondrium, and thickening of GB, whereas conversion to OP was significantly high in patients with thickening of GB and distended or contracted GB.…”
Section: Discussionmentioning
confidence: 67%
“…[9,10] Pre-operative prediction becomes more important so that surgeons can be requested to be present during surgery and to avoid unnecessarily prolonging the surgery and to prevent complications. [11] In the present study, difficult LC was significantly more in patients with a history of previous abdominal surgery, tenderness in right hypochondrium, and thickening of GB, whereas conversion to OP was significantly high in patients with thickening of GB and distended or contracted GB.…”
Section: Discussionmentioning
confidence: 67%
“…In previous reports looking at all gallbladder diseases, a number of risk factors for increased operation length and conversion rates have been established: male sex, previous history of acute cholecystitis, CRP elevation, gallbladder wall thickness, calculi, diabetes mellitus, obesity, and others. 7,[15][16][17][18] In previous studies involving only acute cholecystitis cases, Teckchandani et al 8 indicated that elevated WBC count, CRP, Alkaline phosphate, and amylase, as well as male sex, were risk factors for conversion, and Asai et al 19 identified longer presurgical symptom duration and elevated CRP as risk factors for conversion. Gallbladder thickness has been shown to be a significant predictor of laparoscopic cholecystectomy difficulty in several prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…High efficiency and work rationalization represent advantages of day surgery for doctors. However, it may only be performed by experts who are able to estimate the result of postoperative recovery process (Šoltés & Radoňak, 2014). In Slovakia, 70 % of patients prefer sick leave over day surgery.…”
Section: Introductionmentioning
confidence: 99%